(untitled) (Research, Society and Development, 2024)
This study analyzes the caffeine content and investigates the relationship between the consumption of caffeinated soft drinks and systemic arterial hypertension (SAH), which is a chronic condition that may increase the risk of cardiovascular diseases. Caffeine, an alkaloid in several beverages, has been widely studied for its effects on blood pressure. This article aims to present the research results that focus on the analysis of caffeinated soft drinks, consumed by a wide range of the population, including hypertensive individuals. Regarding the methodology, laboratory research, of a quantitative nature was carried out, which involved the extraction of caffeine from soft drink samples, followed by analysis using UV-Vis detection. Although the results are within the limits of ANVISA for caffeine content, total consumption from various sources, such as coffee and energy drinks, may affect blood pressure. Reviewed studies indicate that caffeine can cause temporary increases in blood pressure, with more pronounced effects in hypertensive individuals. Hypertensive patients need to be cautious and moderate their caffeine intake. However, due to the scarcity, more studies are necessary to evaluate the long-term effects of caffeine in patients with Arterial Hypertension and individualized medical guidance.